Assessing the Biodegradation of Vulcanised Rubber Particles by Fungi Using Genetic, Molecular and Surface Analysis - Andler, R.; D’Afonseca, V.; Pino, J.; Valdés, C.; Salazar-Viedma, M. (Frontiers in Bioengineering and Biotechnology, 2021)
Millions of tonnes of tyre waste are discarded annually and are considered one of the most difficult solid wastes to recycle. A sustainable alternative for the treatment of vulcanised rubber is the use of microorganisms that can biotransform polymers and aromatic compounds and then assimilate and mineralise some of the degradation products. However, vulcanised rubber materials present great resistance to biodegradation due to the presence of highly hydrophobic cross-linked structures that are provided by the additives they contain and the vulcanisation process itself. In this work, the biodegradation capabilities of 10 fungal strains cultivated in PDA and EM solid medium were studied over a period of 4 weeks. The growth of the strains, the mass loss of the vulcanised rubber particles and the surface structure were analysed after the incubation period. With the white rot fungi Trametes versicolor and Pleurotus ostreatus, biodegradation percentages of 7.5 and 6.1%, respectively, were achieved. The FTIR and SEM-EDS analyses confirmed a modification of the abundance of functional groups and elements arranged on the rubber surface, such as C, O, S, Si and Zn, due to the biological treatment employed. The availability of genomic sequences of P. ostreatus and T. versicolor in public repositories allowed the analysis of the genetic content, genomic characteristics and specific components of both fungal species, determining some similarities between both species and their relationship with rubber biodegradation. Both fungi presented a higher number of sequences for laccases and manganese peroxidases, two extracellular enzymes responsible for many of the oxidative reactions reported in the literature. This was confirmed by measuring the laccase and peroxidase activity in cultures of T. versicolor and P. ostreatus with rubber particles, reaching between 2.8 and 3.3-times higher enzyme activity than in the absence of rubber. The integrative analysis of the results, supported by genetic and bioinformatics tools, allowed a deeper analysis of the biodegradation processes of vulcanised rubber. It is expected that this type of analysis can be used to find more efficient biotechnological solutions in the future.